A Lifelong Passion : Nicholas and Alexandra : Their Own Story - Maylunas, Andrei; Mironenko, Sergei (London Weidenfeld & Nicolson, 1996)
Collection of diaries and correspondence between the members of the Russian royal family and their closest friends, from the 1880s to the time of their deaths in 1918.
Include Illustrations, Maps, Sources and Index.
Nicholas and Alexandra's Their Own Story.
Keywords: Kings and rulers -- Alexandra, Empress, consort of Nicholas II, Emperor of Russia, 1872-1918 -- Nicholas II, Emperor of Russia, 1868-1918 -- Russia